IMPLEMENTASI KEBIJAKAN BADAN LAYANAN UMUM DAERAH (BLUD) DI RSUD UNDATA PROVINSI SULAWESI TENGAH - Hasna, Hasna (Katalogis, 2016)
This research aimed at improving and explaining the phenomenon of policy implementation of Regional Public Service Agency in Regional Hospital of Undata.Â The main guided as theory analytic is a model of policy implementation developed by Edward III which consists of aspects of Communication, Resources, Implementersâ€™ Attitude/Dispotition and Bureaucratic Structure. Informants of this research are determined purposively on Undata Hospital employees who are deemed to understand and know about aspects of this research. Research method used is a qualitative method with data colection technique conducted through observation, interviews and documentation. Data were analysed using the Interactive Model by Miles and Huberman namely data collection, data reduction and display and conclusion/verification. The research result shows that the implementation of policy public of regional public service agency policy implemantion on Undata Hospital of Central Sulawesi Province is generally in good enough categories. Of the four aspects investigated, aspect of communication with the dimension of size and objectives and policy target has not been achieved maximally. Then aspect of the resources with the dimension of amount employee reource, competency and skill of employee and facilities is effective enough. On dispotition aspect which consist of supporting, attitude and manner dimensions, has been shown good improvent. In bureaucracy structure with the dimension aspect of standard operational procedure, has been followed propoerly, but it only needs to increase the consistency with more strict rules.